Pengaruh Electronic Word of Mouth terhadap Kepercayaan dan Keputusan Pembelian pada Aplikasi Shopee Mahasiswa Universitas Triatma Mulya - Makur, Bertoldus; Karta , Ni Luh Putu Agustini; Oktaviani, Laras (Penerbit Goodwood, 2022)
Purpose: This study analyzes how electronic word-of-mouth influences trust, examines how trust affects purchase decisions, and investigates how electronic word-of-mouth influences purchase decisions. Methodology: This research was categorized as quantitative descriptive research, with a sample size of 128 respondents, and analyzed using path analysis techniques. Result: The findings of this study indicate that the electronic word-of-mouth variable (X) has a significant influence on the trust variable, as indicated by a t-significance value of 0.000. Trust has a significant influence on purchase decisions, as indicated by the t-significance value of 0.000. The electronic word-of-mouth variable also had a significant influence on the purchase decision variable, as indicated by the t-significance value of 0.000. In this study, there is one independent variable, namely electronic word of mouth (EWOM), and two dependent variables, namely trust and purchase decisions. The relationship between the EWOM variable and purchase decisions is highly significant, with a value of 0.815. This indicates a strong and robust relationship between EWOM and purchase decisions. Additionally, there was a strong relationship between the trust variable and purchase decisions, with a correlation coefficient of 0.742. This suggests that trust also plays a significant role in purchase decision-making, and they exist at Triatma Mulya University.